The Relative Effectiveness of Spot and Derivatives Based Intervention : The Case of Brazil - Nedeljkovic, Milan (IMF Working Papers; Working Paper, 2017)
This paper studies the relative effectiveness of foreign exchange intervention in spot and derivatives markets. We make use of Brazilian data where spot and non-deliverable futures based intervention have been used in tandem for more than a decade. The analysis finds evidence in favor of a significant link between both modes of intervention and the first two moments of the real/dollar exchange rate. As predicted by theory for the case of negligible convertibility risk, the impact of spot market intervention in our baseline sample is strikingly similar to that achieved through futures based intervention worth an equivalent amount in notional principal.